Community Perception of Kuda Lumping Art in The Simpang Kiri Sub-District Subussalam City - Mifta Rahmawati; Maimun Maimun; Hasbi Ali (Jurnal Seni Tari, 2023)
This research is about "public perception of kuda lumping art in Simpang Kiri District, Subulussalam city". The researcher tries to describe: (1) the implementation of kuda lumping art in Simpang Kiri District, Subulussalam city. (2) the public's perception of the presence of kuda lumping art in the city of Subulussalam. The purpose of this study was to find out the implementation and public perception of kuda lumping art. This research belongs to the type of descriptive research with a qualitative approach. While collecting data using interview techniques. Informants in this study amounted to 8 (eight) people. The findings of this study indicate that the implementation of kuda lumping was performed by 8 or more young people who rode horses made of woven bamboo and then dressed in typical Javanese traditional dress and accompanied by musical instruments that were played on the spot. At the end of the event some players will experience a kind of possession. The community accepts the existence of kuda lumping art and is quite enthusiastic about watching this art. Of course, this art reaps good and bad responses from the community. But the community still accepts and expects the preservation of kuda lumping art. The conclusions of this study are: (1) The art of kuda lumping in its implementation is dancing using a piggyback made of woven bamboo directly accompanied by traditional Javanese musical instruments. (2) the art of Kuda Lumping is well received by the people of Subulussalam City without neglecting the existing arts.